P205 Maternal left ventricular global longitudinal strain correlates with parameters of fetal intrauterine growth and uteroplacental hemodynamics. (17th January 2020) - Palermo, C; Muraru, D; Badano, L; Balducci, E; Carli, S; Aruta, P; De Virgilio, A; Pinto, F; Cosmi, E; Visentin, S
Abstract: : Impairment of physiological mechanisms responsible for maternal cardiovascular adaptation during pregnancy may be associated to intrauterine growth restriction (IUGR). Purpose: To compare maternal cardiac parameters between pregnancies with IUGR and with fetal growth appropriate for gestational age (AGA). Methods: Twenty-one IUGR (median age 31 years) were compared with 18 AGA matched for age, body size and gestational age (p > 0.35 for all). LV volumes and ejection fraction (LVEF) were measured by 3D echocardiography, and LV mass (LVM) and outflow velocity time integral (VTI) by conventional echocardiography. LV longitudinal strain (GLS) was assessed by speckle-tracking. Results: Compared to AGA, IUGR mothers had similar LV volumes and LVEF, but larger LV mass (76 vs 63 g/m2, p = 0.006), LV mass/volume (1.14 vs 1.0 g/ml, p = 0.036) and lower VTI (19.9 vs 21.5 cm, p = 0.046) and GLS (-20 vs -22%, p = 0.032). Maternal LV GLS correlated with fetal growth and utero-placental hemodynamics (Table). At ROC curve analysis, maternal GLS had a good ability to discriminate IUGR from AGA (Figure). Conclusions: IUGR had larger LV mass/volume and lower GLS than AGA. GLS was more sensitive than LVEF to detect LV function changes in IUGR. This is the first study reporting that worse maternal LV GLS correlates with fetal growth restriction and suboptimal utero-placental hemodynamics.